COMPARATIVE ANALYSIS OF CLINICAL PERFORMANCE BETWEEN PREP AND NO-PREP FELDSPATHIC VENEERS OVER 10 YEARS - Adrian Jantea; Sorin Gheorghe Mihali; Liliana Porojan; Dan Lolos; Anca Tudor; Mihai Mitariu (Romanian Journal of Oral Rehabilitation)
This study compares the clinical outcomes of two methods for veneer application: the no-prep and prep approaches. A total of 170 patients (108 females, 62 males, mean age 45.2 years) were treated with veneers using either the no-prep or prep method. Clinical evaluations were based on criteria such as esthetic anatomical form, occlusal contour and wear, and periodontal response, measured over a 10-year follow-up period. The results demonstrated that the no-prep method significantly outperformed the prep method in several key areas, including esthetic anatomical form (C3), occlusal contour and wear (C6), and periodontal response (C10), with p-values of 0.038, <0.001, and 0.001, respectively. The no-prep method also showed superior performance in terms of recurrent caries (C8). These findings suggest that the no-prep method provides notable advantages in both functionality and esthetics, leading to better long-term clinical outcomes compared to the prep method, when correctly applied to the patient case.